Reinforced concrete design to EuroCode 2 (EC2) - Mosley, W. H. (William Henry) (Macmillan, 1996)
This text is developed from the established and well-known textbook Reinforced Concrete Design. It adopts the same format of presentation to cover the design and detailing of reinforced and prestressed concrete members and structures to the new Eurocode for the design of concrete structures (Eurocode 2: Design of Concrete Structures, Part 1). The book aims to give a straightforward and practical introduction to the principles and methods used in the design of reinforced and prestressed concrete structures and presents numerous worked examples to illustrate the various aspects of design. Although the detailed methods considered are generally according to EC2 much of the theory presented is also of a fundamental nature. Appropriate design charts, tables and formulae are presented as design aids and, for ease of reference, a summary of important design equations together with design tables and charts are presented in the Appendix.